Marginal Adaptation of New Bioceramic Materials and Mineral Trioxide Aggregate: A Scanning Electron Microscopy Study - Shokouhinejad, Noushin; Nekoofar, Mohmmad Hossein; Ashoftehyazdi, Kazem; Zahraee, Shohreh; Khoshkhounejad, Mehrfam (Iranian Endodontic Journal, 2014)
Introduction: This study aimed to compare the marginal adaptation of new bioceramic materials, EndoSequence Root Repair Material (ERRM putty and ERRM paste), to that of mineral trioxide aggregate (MTA) as root-end filling materials. Materials and Methods: Thirty-six extracted human single-rooted teeth were prepared and obturated with gutta-percha and AH-26 sealer. The roots were resected 3 mm from the apex. Root-end cavities were then prepared with an ultrasonic retrotip. The specimens were divided into three groups (n=12) and filled with MTA, ERRM putty or ERRM paste. Epoxy resin replicas from the resected root-end surfaces and longitudinally sectioned roots were fabricated. The gaps at the material/dentin interface were measured using scanning electron microscope (SEM). Transversal, longitudinal, and overall gap sizes were measured for each specimen. The data were analyzed using the Kruskal-Wallis test. Results: In transversal sections, no significant difference was found between MTA, ERRM putty and ERRM paste (P=0.31). However, in longitudinal sections, larger gaps were evident between ERRM paste and dentinal walls compared to MTA and ERRM putty (P=0.002 and P=0.033, respectively). Considering the overall gap size values, the difference between three tested materials was not statistically significant (P=0.17). Conclusion: Within the limits of this study, the marginal adaptation of ERRM paste and putty was comparable to that of MTA. However, ERRM putty might be more suitable for filling the root-end cavities because of its superior adaptation compared to ERRM paste in longitudinal sections.